2016
DOI: 10.1038/modpathol.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Disease-specific survival of patients with invasive cribriform and intraductal prostate cancer at diagnostic biopsy

Abstract: Invasive cribriform and intraductal carcinoma in radical prostatectomy specimens have been associated with an adverse clinical outcome. Our objective was to determine the prognostic value of invasive cribriform and intraductal carcinoma in pre-treatment biopsies on time to disease-specific death. We pathologically revised the diagnostic biopsies of 1031 patients from the first screening round of the European Randomized Study of Screening for Prostate Cancer (1993Cancer ( -2000. Ninety percent of all patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
189
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(197 citation statements)
references
References 26 publications
5
189
1
2
Order By: Relevance
“…Secondly, this might be a reflection of the heterogeneity of Gleason pattern 4, which is not addressed by GG and can have a significant prognostic/clinical impact. Kweldam et al 17 reported the lack of consensus between expert genitourinary pathologists on ill-formed or complex fused glands, describing this as a borderline pattern of unknown prognostic significance; while cribriforming and intraductal patterns 4 are less ambiguous, and associated with poorer prognosis,18 often leading to upgrading of GG2 disease at RP 19. Reflecting these challenges, reporting the proportion of pattern 4 cancer on biopsies has recently been recommended by the ISUP as a Gleason grading refinement 20.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this might be a reflection of the heterogeneity of Gleason pattern 4, which is not addressed by GG and can have a significant prognostic/clinical impact. Kweldam et al 17 reported the lack of consensus between expert genitourinary pathologists on ill-formed or complex fused glands, describing this as a borderline pattern of unknown prognostic significance; while cribriforming and intraductal patterns 4 are less ambiguous, and associated with poorer prognosis,18 often leading to upgrading of GG2 disease at RP 19. Reflecting these challenges, reporting the proportion of pattern 4 cancer on biopsies has recently been recommended by the ISUP as a Gleason grading refinement 20.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,13 In 2005, the International Society of Urological Pathology (ISUP) assigned a Gleason grade 4 rather than Gleason grade 3 for a cribriform pattern. 8,9 In 2009, Lotan et al showed that there was often histologic continuity between glomeruloid glands and cribriform pattern.…”
Section: Cribriform Pattern In Invasive Prostate Cancermentioning
confidence: 99%
“…Now, it is well established that IDC represents a histopathological entity associated with higher Gleason score and advanced pathological stage . Moreover, both in prostate biopsy and radical prostatectomy specimens, its presence is a strong and independent prognosticator of metastatic disease and death of disease . Further, its presence in biopsies was shown to be associated with more advanced pathological stage at the time of prostatectomy .…”
Section: Introductionmentioning
confidence: 97%